Pengaruh Brand Awareness dan Harga terhadap Keputusan Pembelian Parfum Scarlett di Shopee - Siti Robiah Al Adawiah; Mulyadi Suhardi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among local perfume brands, particularly on marketplace platforms such as Shopee. In this competitive environment, brand awareness and price are considered strategic factors influencing consumers’ purchase decisions. This study aims to examine the effect of brand awareness and price on purchase decisions for Scarlett perfume products on Shopee, both partially and simultaneously. This research employs a quantitative approach using a survey method with 96 respondents who have previously purchased Scarlett perfume on Shopee. Data analysis was conducted using multiple linear regression, supported by classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that brand awareness has a positive and significant effect on purchase decisions. Price also shows a positive and significant influence on purchase decisions. Simultaneously, brand awareness and price significantly affect purchase decisions, with an R² value of 0.776. These findings highlight the importance of strengthening brand awareness alongside appropriate pricing strategies to enhance consumers’ purchase decisions for local perfume products in digital marketplace environments.